MERANCANG STRATEGI KOMUNIKASI MELAWAN RADIKALISME AGAMA - Utomo, Gondo (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2016)
The views, solicitation, or radical movements in the name of Islam is increasingly widespread. In various forms, the radicalism in the name of religion prompted an act of suicide bomb wrapped in jihad, hate speech over others, and disseminating views on religion despite the obligation to fight it through violence. Religious radicalism can only be combated using anti religious radicalism, which is now constantly made parties. This article analyzes the importance of planning communication strategy in order solicitation dissemination, understanding, a nd views on the importance of action away from radical religious order solicitation dissemination, understanding and views in the form of information campaigns that get the desired results.